A study on the diaper choice of selected consumers - Orquieza, Vanessa Noella M. (UP College of Home Economics, 2012)
The descriptive research aimed to explore the diaper choices of selected consumers and the reasons behind their choices. Data was collected through an online survey answered by 60 purposively selected respondent. Caregivers and parents of children in diapers from 0-36 months old were targeted. The questionnaire explored the respondents' profile, diaper choice, reasons for the choice, awareness on the possible risks of disposable diapers, willingness of non cloth users to switch and why. Disposable diapers dominate over cloth diapers in terms of diaper choice. Majority of he consumers choose disposable diapers for the convenience the give. Factors pertaining to the wellbeing of the child, like absorbency and rash prevention, ar top priority in diaper selection. However, factors pertaining to ease for the caregiver, like convenience of use, play a huge role while environmental concerns are unimportant. This study shows that consumers do not believe that disposable diapers pose any harm for the child. They choose disposable diapers since these fulfill both their concern for the child's wellbeing as well as ease for themselves. Consumers are willing to pay the price of added convenience. Cloth diapers are generally avoided because of the washing needed. The study proved that demographic factors like income have no significant relation to the type of diaper used. It also shows that here is a need for awareness on the possible risks of disposable diapers. Some consumers would be willing to switch to cloth diapers if they find out that wellbeing of the child is compromised by their choice.